Meat Animal Biologics Discovery Opportunities from the Gut Microbiome: Application of Metabolomics - Chamia C Chatman; Elena Olson; Erica L-W Majumder; Hilario C Mantovani; Steven C Ricke (Meat and Muscle Biology)
Metabolomics is a high-throughput technology that is widely used across disciplines to identify and quantify metabolites in biological samples; however, its use has been limited in meat and animal science. The use of metabolomics, especially in these fields, is often curtailed by challenges with data processing and analysis. Improvements in data analysis platforms have broadened metabolomics applications and offer promise for determining metabolic pathways that directly influence animal health and livestock production. This review will present an overview of metabolomics concepts and current applications of metabolomics techniques in meat and animal science. Furthermore, we present evidence of the need to incorporate metabolomics in a systems biology context for the improvement of livestock production with an emphasis on animal health and production efficiency.